Immunological Memory and Affinity Maturation After Vaccination in Patients With Propionic Acidemia - Zlamy, Manuela; Zöggeler, Thomas; Bachmann, Magdalena; Schirmer, Michael; Lechner, Christian; Michel, Miriam; Schimkowitsch, Alexander; Karall, Daniela; Scholl-Bürgi, Sabine (Frontiers in Immunology, 2022)
Earlier studies have recommended routine childhood immunization in patients with propionic acidemia (PA); however, the literature presents insufficient data on the response to vaccines, notably specific IgG concentrations and avidity maturation, after measles, mumps, rubella (MMR), and diphtheria/tetanus (DiphtTe) vaccinations in this population. In patients with PA, cellular and humoral changes of the immune system (e.g. a decreased CD4+ T cell count, with a reversal of CD4/CD8 T cell ratio, a deficient gamma-globulin fraction, and in one case a decreased lymphocyte blastogenesis) have been reported. Former reports also detected pancytopenias accompanying febrile infections in PA patients. In the current study, we analyzed vaccine-specific IgG concentrations and avidity maturation after MMR and DiphtTe vaccinations in 10 patients with PA. Compared to gender and age matched controls, all 10 had protective IgG concentrations for at least one tested antigen, and in 6 out of 10 patients high relative avidity indices for measles and rubella were detected. In summary, the present study revealed a sufficient immune response and outcome, indicating an acceptable humoral memory in patients with PA after booster vaccinations.